Komunikasi Persuasif Terkait Kesadaran Kesehatan Mental dalam Series “Daily Dose of Sunshine”: Analisis Semiotik Ferdinand De Saussure - Hafizah, Nur; Fatimah, Anggun Nadia; Rizki, Menati Fajar (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Persuasive communication is a strategy employed to convince and influence others to accept a message without imposing pressure, while still allowing them the freedom to either accept or reject it.In 2023, a medical-themed series titled "Daily Dose of Sunshine" was released, addressing mental health issues. Such series play a vital role in raising awareness and understanding of these issues among the public. This research aims to examine the persuasive communication used by doctors and nurses towards patients regarding mental health awareness in "Daily Dose of Sunshine." The qualitative analysis employs Ferdinand de Saussure's semiotic method, focusing on signifiers and signifieds. Data comprise dialogue excerpts and images from the series. Results reveal persuasive communication techniques such as framing, integration, payoff, and fear arousing, predominantly conveyed through direct verbal communication. Supporting factors include the credibility and attractiveness of communicators. Feedback from persuadees indicates acceptance of persuasive messages, leading to increased openness and positive actions as advised by medical professionals.